HUBUNGAN PERAN KELUARGA TERHADAP PENYESUAIAN DIRI REMAJA - Jon Iskandar Bahari (INCARE, International Journal of Educational Resources, 2020)
The research begins with some of the fact that many teenagers are experiencing failures in their adjustments. The failure is provoke by problems with families such as the economic status of middle-aged parents, very busy parents working, the elderly who are less attentive to their children, the elderly are too authoritarian that causes the child to lack self-esteem, not confident, low-learning achievement, less able to associate with friends, so that the child becomes naughty The purpose of this study is to know the correlation of family roles on adolescent self-adaptation. This research uses quantitative methods. Independent variables are family and dependent variables are self-adjusting. Subjects numbered 125 respondents were selected using the random sampling technique. In data collection, researchers use methods in the form of Likert scale. Data analysis uses the correlation technique of Product moment Karl Person, with SPSS version 17.0 for Windows.